ANALISIS PERBANDINGAN TEBAL PERKERASAN LENTUR METODE ANALISA KOMPONEN DENGAN MDPJ 2017 (Studi Kasus: Jalan Nagari Bungo Tanjuang Kabupaten Tanah Datar) - Ilham Chalik; Surya Eka Priana; Febrimen Herista (Progressive Journal of Advanced Engineering and Technology, 2026)
Parking facilities are inseparable in driving life. Parking facilities are a matter of considerable concern, especially when visiting places that are densely packed with visitors such as public service centers, for example the Lubuk Attitudeing Health Center. Puskesmas usually have a busy schedule of visitors at certain hours every day so that problems occur such as the lack of availability of parking areas. To overcome this problem, it is necessary to identify the availability of parking areas at the Lubuk Attitudeing Health Center by analyzing the characteristics and level of parking services at the health center, the characteristics analyzed are parking volume, parking accumulation, parking index, parking turnover rate, usage rate and parking capacity. From the results of research conducted for 5 working days, (July 15-19 2023) from 08.00-13.00 WIB (Puskesmas operational hours) and data processing was carried out, it can be concluded that: the largest number of vehicles that entered was 4 cars on Tuesday under 08:00 WIB and 17 motorcycles on Tuesday at 08.00-09.00 WIB, the largest accumulation was 6 cars on Monday and 27 motorbikes on Wednesday, the largest volume of parking for cars was 5 vehicles on Monday and motorcycles namely 33 vehicles on Wednesday, and the capacity of the parking area at the Lubuk Attitudeing Health Center is 7 SRP for cars and 52 SRP for motorcycles.Keywords: Parking Facilities. Parking Characteristics, Parking Area Capacity.